Recent advances and future perspectives for aqueous zinc-ion capacitors. (1st June 2022) - Huang, Zhaodong; Zhang, Rong; Zhang, Shaoce; Li, Pei; Li, Chuan; Zhi, Chunyi
Abstract: Ion-hybrid capacitors are expected to combine the high specific energy of battery-type materials and the superior specific power of capacitor-type materials and are considered as a promising energy storage technique. In particular, aqueous zinc-ion capacitors (ZIC), possessing the merits of high safety, cost-efficiency and eco-friendliness, have been widely explored with various electrode materials and electrolytes to obtain excellent electrochemical performance. In this review, we first summarize the research progress on enhancing the specific capacitance of capacitor-type materials and review the research on improving the cycling capability of battery-type materials under high current densities. Then, we look back on the effects of electrolyte engineering on the electrochemical performance of ZIC. Finally, we propose research challenges and development directions for ZIC. This review provides guidance for the design and construction of high-performance ZIC.